Indication of Moral Erosion in Children’s Fiction - Wahyu Wiji Astuti; M Anggie J Daulay; M Oky F Gafary (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
Children literature has an important role in children development. Based on the research, there is a different between intellectual and character from child who is a bookworm and who is not. Reading fiction is a favorite of children. Children tend to identify themselves into a character in a fiction, therefore proper rules needs to be put into consideration. This paper aims at underlining problems in children fiction which are potentially eroding children’s morality. Analysis is done by studying the value and structure in children’s literature. It needs to be reconstructed, so reading habit of children will not drop them down to moral erosion.